2017
DOI: 10.18632/oncotarget.20276
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in pre-miRNAs predict the survival of non-small-cell lung cancer in Chinese population: a cohort study and a meta-analysis

Abstract: BackgroundTo explore the association of genetic polymorphisms in pre-miRNA 30c-1 rs928508 and pre-miRNA 27a rs895819 with non-small-cell lung cancer prognosis.Materials and Methods480 patients from five hospitals were enrolled in this prospective cohort study. They were followed up for five years. The association between genotypes and overall survival was assessed by Cox proportional hazards regression models. A meta-analysis was conducted to provide evidence for the effect of microRNA 27a rs895819 on cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, three meta-analyses including the last from 2021 which claimed to provide a more accurate evaluation of all published eligible studies showed that the wild-type AA genotype rs895819 was associated with increased susceptibility to breast cancer among Caucasians but not among Asians while harboring G-allele and AG genotype might have a protective role [ 129 , 130 , 131 ]. The C (G) allele of rs895819 was associated with shorter overall survival and increased risk of death than the T (A) allele in Asian patients with non-small cell lung cancer [ 132 , 133 ]. According to Xia et al (2017), the polymorphism in miRNA-27a could predict not only the outcome of non-small cell lung cancer patients but also might decrease the sensitivity to anti-cancer drugs [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, three meta-analyses including the last from 2021 which claimed to provide a more accurate evaluation of all published eligible studies showed that the wild-type AA genotype rs895819 was associated with increased susceptibility to breast cancer among Caucasians but not among Asians while harboring G-allele and AG genotype might have a protective role [ 129 , 130 , 131 ]. The C (G) allele of rs895819 was associated with shorter overall survival and increased risk of death than the T (A) allele in Asian patients with non-small cell lung cancer [ 132 , 133 ]. According to Xia et al (2017), the polymorphism in miRNA-27a could predict not only the outcome of non-small cell lung cancer patients but also might decrease the sensitivity to anti-cancer drugs [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…The C (G) allele of rs895819 was associated with shorter overall survival and increased risk of death than the T (A) allele in Asian patients with non-small cell lung cancer [ 132 , 133 ]. According to Xia et al (2017), the polymorphism in miRNA-27a could predict not only the outcome of non-small cell lung cancer patients but also might decrease the sensitivity to anti-cancer drugs [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs polymorphisms have been reported to influence the expression of mature miRNAs (13, 14). For instance, Chen et al have reported that micRNA30c-1 polymorphisms could regulate the expression of mature miRNA 30c-1 and thus affect cancer prognosis (15, 16). A research by Yu et al suggested the rs4938723 polymorphism could reduce micRNA-34b expression and increase the recurrence of early gastric cancer (17).…”
Section: Introductionmentioning
confidence: 99%